Riding the Waves of Change: The Future of Education 2030 and Beyond - Made Novia Indriani; I Gusti Ayu Asri Pramesti; Juniati Gunawan; John Lee CG; Sean Patrick Rozario; Christina Tian (Asia Pacific Journal of Management and Education (APJME), 2024)
Entering the current era of globalization, there have been many changes, such as climate, health, and welfare, which of course require balanced adaptation and education. This research aims to provide educational changes with the adaptation of the younger generation to cope with climate and environmental changes. The changes needed include curriculum, educator mindset, infrastructure, and teaching methods. This research uses qualitative methods for analysis and evaluation. The research process was conducted through literature studies, discussions, and observations to obtain solutions to the phenomena that occurred. There are four important things that need to be considered related to the phenomenon, namely climate, health, welfare, and education in Indonesia. Based on the results of the study and discussion, it can be concluded that climate, health, welfare, and education play an important role in creating change, including from universities. Prioritizing the development of educational institutions that are modern, ethical, responsible, responsive, and have complete facilities is the main way to create equal access to education. This study contributes to the importance of facing the wave of change and preparing to create a new education in the future.